Análisis y perspectivas de las pruebas confesional, documental y pericial en materia mercantil - Reséndiz García, Jorge (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
With the motive of the reform that diverse articles from the Code of Commerce were object through legislative decrees published in the Official Newspaper of the Federation dated May 24 th , 1996, and June 13 th 2003, specifically with respect to the offering, admission, preparation and release of confessional, expert and documental proofs, diverse ambiguities, vagueness and antinomies were generated. Referent to the confessional proofs, two terms have been established to offer it and the article 1214 contains a deficient and obscure writing that is not congruent with the provided procedure for the ordinary trial and commercial executive trial. With respect to the documentary evidence, reading the articles 1244, 1247, 1250, 1251 and 1297 is appreciated that exists duplicity of time limit and procedures exist for the objection of documents, lack of forecast of the effects of the sentence that decrees the origin of the objection and a generic regulation for the recognition of the documents, not making any distinction if they come from some of the parts or from a third one. And with respect to the expert proofs, a plurality of procedures is contemplated for its admission, preparation and release. The intended purpose of the present research job is based on determining: ¿When the confessional proofs must be offered depending whether it is an ordinary commercial trial or a commercial executive trial And to which audience refers the article 1214 of the Code of Commerce? ¿Which term should be observed with the purpose to object a document, the procedure to follow to object a document, the effects of the sentence that decrees the proceeding of the objection of a document, and the procedure to recognize a document, depending if it comes from the parts or from a third party?. ¿Which procedure must be followed for the offering, admission, preparation and release of the expert evidence proof depending on its matter of commercial ordinary trial, commercial executive trial, or execution of a sentence?

Con el motivo de la reforma que diversos artículos del Código de Comercio eran objeto a través de decretos legislativos publicados en el Diario Oficial Periódico de la Federación de fecha 24 de mayo de 1996 y 13 de junio de 2003, específicamente con respecto a la oferta, la admisión, la preparación y liberación de, expertos y documentales pruebas confesionales, diversas ambigüedades, vaguedades y Se generaron antinomias. Referente a las pruebas confesionales, dos términos tienen ha establecido para ofrecerlo y el artículo 1214 contiene una deficiente y oscura escritura que no es congruente con el procedimiento previsto en el juicio ordinario y juicio ejecutivo mercantil. Con respecto a la prueba documental, la lectura de la artículos 1244, 1247, 1250, 1251 y 1297 se aprecia que existe duplicidad de existen límites y procedimientos de tiempo para la objeción de los documentos, la falta de previsión de los efectos de la sentencia que decreta el origen de la objeción y un genérico la regulación para el reconocimiento de los documentos, no hacer distinción si venir de alguna de las partes o de un tercero. Y con respecto a la experto pruebas, una pluralidad de procedimientos se contempla para su admisión, preparación y liberación. La finalidad del presente trabajo de investigación se basa en la determinación de: ¿Cuando las pruebas confesionales deben ser ofrecidos en función de si se trata de un prueba comercial ordinario o un juicio ejecutivo mercantil, así como que la audiencia se refiere el artículo 1214 del Código de Comercio? ¿Qué término debe ser observada con el propósito de objetar un documento, el procedimiento a seguir para objetar un documento, los efectos de la sentencia que decreta el procedimiento de la objeción de un documento, y el procedimiento para reconocer a un documento, dependiendo de si se trata de las partes o de un tercero ?. ¿Qué procedimiento se debe seguir para la ofrenda, la admisión, la preparación y la liberación de la prueba pericial en función de su carácter comercial juicio ordinario, juicio ejecutivo mercantil, o la ejecución de una pena?
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2006-0002; Mercantil; Confesional; Documental; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/422